2015
DOI: 10.1177/2156587215583756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Topical Saffron (Crocus sativus L) Gel on Erectile Dysfunction in Diabetics

Abstract: Erectile dysfunction is a man's persistent or recurrent inability to achieve and maintain erection for a satisfactory sexual relationship. As diabetes is a major risk factor for erectile dysfunction, the prevalence of erectile dysfunction among diabetic men has been reported as 35% to 90%. This randomized, parallel-group, double-blind, placebo-controlled trial investigated the effects of a topical saffron (Crocus sativus L) gel on erectile dysfunction in diabetic men. Patients were randomly allocated to 2 equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Saffron tea has been reputed to be a potential complementary treatment for psoriasis in medical nutrition therapy [13]. Many pharmacological studies have shown that this plant and its phytochemicals have emerged as nutraceutical elements, endowed with beneficial effects on health showing antibacterial [14], antioxidant, cytotoxic [15,16], antifungal [17], immunomodulatory [18,19], anti-mutagenic [20], aphrodisiac [21], antitussives [22,23], and antiplatelet effects [24]. Traditional and modern biomedical reports have also proved saffron to cure coronary artery diseases [25], respiratory diseases [26], menstrual disorders [27,28], and neurodegenerative disorders [29].…”
Section: Introductionmentioning
confidence: 99%
“…Saffron tea has been reputed to be a potential complementary treatment for psoriasis in medical nutrition therapy [13]. Many pharmacological studies have shown that this plant and its phytochemicals have emerged as nutraceutical elements, endowed with beneficial effects on health showing antibacterial [14], antioxidant, cytotoxic [15,16], antifungal [17], immunomodulatory [18,19], anti-mutagenic [20], aphrodisiac [21], antitussives [22,23], and antiplatelet effects [24]. Traditional and modern biomedical reports have also proved saffron to cure coronary artery diseases [25], respiratory diseases [26], menstrual disorders [27,28], and neurodegenerative disorders [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the effects of crocin intake on sexual functions in individuals not undergoing MMT, though data on the effects of crocin administration on sexual function in patients under MMT are scarce. Saffron administration significantly improves erectile dysfunction in diabetic patients [40]. In a study conducted by Shamsa et al [20], oral saffron administration at a dose of 200 mg/day for 10 days improved erectile function in males suffering from erectile dysfunction [41].…”
Section: Discussionmentioning
confidence: 99%
“…That study demonstrated that use of 15 mg C. sativus twice a day caused improvement of erectile dysfunction in these men 33 . In patients with diabetes, the local application of C. sativus gel leads to treatment of erectile dysfunction 36 . A study reported that treatment with 200 mg of C. sativus a day improved tip rigidity and tip tumescence as well as base rigidity and base tumescence in studied people 37 .…”
Section: Libido-boosting Plant-based Compoundsmentioning
confidence: 99%